Prognostic value of site-specific extra-hepatic disease in hepatocellular carcinoma: a SEER database analysis. (3rd July 2017) - Oweira, Hani; Petrausch, Ulf; Helbling, Daniel; Schmidt, Jan; Mehrabi, Arianeb; Schöb, Othmar; Giryes, Anwar; Abdel-Rahman, Omar
ABSTRACT: Background : We the prognostic value of site-specific extra-hepatic disease in hepatocellular carcinoma (HCC) patients registered within the surveillance, epidemiology and end results (SEER) database. Methods : SEER database (2010–2013) has been queried through SEER*Stat program to determine the prognosis of advanced HCC patients according to the site of extra-hepatic disease. Survival analysis has been conducted through Kaplan Meier analysis. Results : A total of 4396 patients with stage IV HCC were identified in the period from 2010–2013 and they were included into this analysis. Patients with isolated regional lymph node involvement have better outcomes compared to patients with any other site of extra-hepatic disease (P < 0.0001 for both endpoints). Among patients with distant metastases, patients with bone metastases have better outcomes compared to patients with lung metastases (P < 0.0001 for both endpoints). Multivariate analysis revealed that younger age, normal alpha fetoprotein, single site of extra-hepatic disease, local treatment to the primary tumor and surgery to the metastatic disease were associated with better overall survival and liver cancer-specific survival. Conclusion : Within the limits of the current SEER analysis, HCC patients with isolated lung metastases seem to have worse outcomes compared to patients with isolated bone or regional nodal metastases.​